“FUTEBOL À TARDINHA”: NOTES ABOUT EDUCABILITY (Fiep Bulletin - online, 2015)
This study is a investigation about the ways of interventions of soccer in the subjectivity of young people from popular classes. As empirical sample of the research we delimited the Project of extension “Futebol à Tardinha” (Evening Soccer), which occurs three times a week at ESEF/UFPel since 2001. Utilizing a methodology that associates image sources (photographes), oral relates and observant participation we analyzed how the participation in the Project is reconfiguring the subjectivity of its participants, intervining in the friendship relations, in the behavior and in the sociability of these children and young people.
Keywords: Soccer; sociability; youngsters.